TANTANGAN PERBANKAN SYARIAH DALAM MENGHADAPI AFTA 2003 - Sofyan S Harahap (Media Riset Bisnis & Manajemen, 2001)
The Islamic banking systemin Indonesia has been started since 1991. The dəvelopment of this type of banks is encouraging even now its share is 0,2 %. There are 2 full Islamic banks 55 branches and 83 Rural Islamic Banks plus 2500 BMTS (micro Islamic financialinstitutions). Ina year ahead there will be an AFTA in which foreign banks may enter banking market in the country. Whatproblems will be faced by Islamicbanks in that period will be the main focus of this paper. The paper also recommends policies and tasks that may be setby Islamicbank, central bank as well as Muslim community.